2021
DOI: 10.1016/j.euo.2021.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Front-line Therapy for Urothelial Cancer

Abstract: The role of immune checkpoint inhibitors (ICIs) in urothelial cancer (UC) remains in flux. However, three recent randomised trials in the first-line setting have clarified many of the outstanding issues and are discussed here [1][2][3].To date, PD-1 and PD-L1 inhibitors are established as second-line therapy after first-line platinum-containing chemotherapy (CT) [4,5]. This strategy was based on a positive phase 3 randomised trial investigating pembrolizumab versus CT [4]. Debate around the role of the biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In recent years, the use of ICIs has made irreplaceable achievements in the treatment of BC. Atezolizumab and pembrolizumab targeting PD-1 have been approved as first-line treatment for cisplatin-ineligible metastatic urothelial BC by the Food and Drug Administration [51][52][53][54] 'Cold' tumor with low T cell infiltration is a critical reason for the resistance to immunotherapy [55,56]. It is essential to determine tumor immune cell infiltration to understand tumor progression and improve the response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of ICIs has made irreplaceable achievements in the treatment of BC. Atezolizumab and pembrolizumab targeting PD-1 have been approved as first-line treatment for cisplatin-ineligible metastatic urothelial BC by the Food and Drug Administration [51][52][53][54] 'Cold' tumor with low T cell infiltration is a critical reason for the resistance to immunotherapy [55,56]. It is essential to determine tumor immune cell infiltration to understand tumor progression and improve the response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Szabados et al. identified that immune checkpoint inhibitor monotherapy is not superior to chemotherapy as things currently stand, and the chemo-immunotherapy combination showed a probable efficacy signal, but this appeared to be insufficient to change practice ( 49 ). Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of avelumab as maintenance within 10 weeks of completion of first-line chemotherapy has also been shown to significantly improve OS among patients with mUC who had diseases that had not progressed with first-line chemotherapy in the phase III JAVELIN Bladder 100 trial (NCT02603432). The addition of avelumab to best supportive care is associated with an increase in median OS from 14.3 to 21.4 months with avelumab and a HR of 0.69 (95%CI: 0.56-0.86, P = 0.001) [29] .…”
Section: Maintenance Immune Therapymentioning
confidence: 96%
“…The combination ADCs together with immune therapy also shows promising new targets in phase I studies. The EV-103 study (NCT03288545) of EV in combination with pembrolizumab as first-line therapy for patients with mUC, ineligible to receive cisplatin, showed an ORR of 73.3% [29] . Results from the ongoing randomized study EV-302 (NCT04223856), comparing EV plus pembrolizumab to standard-of-care chemotherapy in the front-line setting, are awaited.…”
Section: Novel Immune Combinationsmentioning
confidence: 99%